Introduction to research in the health sciences - Polgar, Stephen; Thomas, Shane A. (Edinburgh : Churchill Livingstone/Elsevier, 2013)
This popular textbook provides a concise, but comprehensive, overview of health research as an integrated, problem-solving process. It bridges the gap between health research methods and evidence-based clinical practice, making it an essential tool for students embarking on research. Practitioners also benefit from guidance on interpreting the ever-expanding published research in clinical and scientific journals, to ensure their practice is up to date and evidence-based and to help patients understand information obtained online.
Section 1. Methodological foundations of health research : Foundations of health research ; Quantitative and qualitative methods ; The research process -- Section 2. Research planning : The formulation of research questions ; Sampling methods and external validity ; Ethics -- Section 3. Research designs : Experimental designs and randomized controlled trials ; Surveys and quasi-experimental designs ; Single case (n = 1) designs ; Qualitative research -- Section 4. Data collection : Questionnaires ; Interviewing techniques ; Observation ; Measurement -- Section 5. Descriptive statistics : Organization and presentation of data ; Measures of central tendency and variability ; Standard scores and normal distributions ; Correlation -- Section 6. Data analysis and inference : Probability and confidence intervals ; Hypothesis testing: selection and use of statistical tests ; Effect size and the interpretation of evidence ; Qualitative data analysis -- Section 7. Evaluation and dissemination of research results : Critical evaluation of published research ; Synthesis: systematic reviews and meta-analysis.
Previous ed.: Edinburgh: Churchill Livingstone Elsevier, 2008.
Includes bibliographical references and index.
Keywords: Biomedical Research -- methods; Research design; Medicine -- Research; Medicine -- Research